The effect of racial and gender concordance between physicians and patients on the assessment of hospitalist performance: a pilot study - Damian Crawford; Suchitra Paranji; Shalini Chandra; Scott Wright; Flora Kisuule (BMC, 2019)
Abstract Background Lack of racial concordance between physicians and patients has been linked to health disparities and inequities. Studies show that patients prefer physicians who look like them; however, there are too few underrepresented minority physicians in the workforce. Hospitalists are Internal Medicine physicians who specialize in inpatient medicine. At our hospital, hospitalists care for 60% of hospitalized medical patients. We utilized the validated Tool to Assess Inpatient Satisfaction with Care from Hospitalists (TAISCH) to assess the effect of patient-provider race and gender concordance on patients' assessment of their physician's performance. Methods Four hundred thirty-seven inpatients admitted to the non-teaching hospitalist service, cared for by a unique hospitalist physician for two or more consecutive days, were surveyed using the validated TAISCH instrument. The influence of gender and racial concordance on TAISCH scores for patient - hospitalist pairs were assessed by comparing the specific dyads with the overall mean scores. T-tests were used to compare the means. Generalized estimating equations were used to account for clustering. Results Of the 34 hospitalist physicians in the analysis, 20% were African American (AA-non-Hispanic), 15% were Caucasians (non-Hispanic) and 65% were in the "other" category. The "other" category consisted of predominantly physicians of South East Asian decent (i.e. Indian subcontinent) and Hispanic. Of the 437 patients, 66% were Caucasians, and 32% were AA. The overall mean TAISCH score, as these 437 patients assessed their hospitalist provider was 3.8 (se = 0.60). The highest mean TAISCH score was for the Caucasian provider-AA patient dyads at 4.2 (se = 0.21, p = 0.05 compared to overall mean). The lowest mean TAISCH score was 3.5 (se = 0.14) seen in the AA provider/AA patient dyads, significantly lower than the overall mean (p = 0.013). There were no statistically significant differences noted between mean TAISCH scores of gender and racially concordant versus discordant doctor-patient dyads (all p's > 0.05). Conclusions In the inpatient setting, it appears as if neither race nor gender concordance with the provider affects a patient's assessment of a hospitalist's performance.